2013
DOI: 10.1590/s1413-81232013000500025
|View full text |Cite
|
Sign up to set email alerts
|

Níveis tensionais de adultos indígenas Suruí, Rondônia, Brasil

Abstract: Níveis tensionais de adultos indígenas Suruí, Rondônia, BrasilBlood pressure levels of Suruí indigenous adults in Rondônia, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 20 publications
2
21
0
4
Order By: Relevance
“…Other studies have focused on the prevalence of HBP in adult indigenous peoples using the same diagnostic criteria as ours and found lower prevalence rates and lower mean SBP and DBP 5,26,30,31,32 . Among the Parkatêjê in Pará State, the prevalence rates for high blood pressure were 3.6% in men and 5.9% in women 29 .…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Other studies have focused on the prevalence of HBP in adult indigenous peoples using the same diagnostic criteria as ours and found lower prevalence rates and lower mean SBP and DBP 5,26,30,31,32 . Among the Parkatêjê in Pará State, the prevalence rates for high blood pressure were 3.6% in men and 5.9% in women 29 .…”
Section: Discussionsupporting
confidence: 67%
“…A study by Gimeno et al 31 among the Mehináku, Waurá, and Yawalapití in the Upper Xingu found prevalence rates of 10.8% in men and 6% in women. Among the Suruí, in Rondônia State, prevalence was 2.4% in men and 3.1% in women 5 . Meyerfreund et al 32 recorded an overall prevalence of 20.8% in the Tupinikim in Espírito Santo State.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations